Altered amino acid levels in young hypopituitarism: impact of NAFLD and insulin resistance - Yuwen Zhang; Jiting Qiu; Shouyue Sun; Xuqian Fang (Amino Acids)
Abstract Elevated concentrations of amino acids (AAs) are commonly observed in patients with nonalcoholic fatty liver disease (NAFLD). Individuals with hypopituitarism (HP) are at a heightened risk of developing NAFLD due to factors such as visceral obesity, increased insulin resistance (IR), and disturbances in lipid metabolism. However, the changes in AAs concentrations associated with HP remain poorly understood. Therefore, our study aimed to investigate whether individuals with HP, who were not receiving growth hormone replacement therapy (GHRT), exhibited altered AAs compared to controls (CTs), and whether these AAs were associated with IR, the presence of NAFLD, and the Metabolic Syndrome (MetS) score. The AAs profiles of 133 young males with HP (age: 24.5 ± 5.9; 57 with NAFLD and 76 without NAFLD) and 90 age and BMI-matched CTs were analyzed using untargeted metabolomics. The results revealed that most AAs were found to be elevated in subjects with HPs compared to CTs. Glutamate, glutamine, norleucine, and branched-chain amino acids (BCAAs) (leucine and valine) were correlated with the homeostasis model assessment of insulin resistance (HOMA-IR), with glutamate and norleucine showing independent linkage. Glutamate and proline levels were specifically associated with MetS score, while alanine and proline linked to NAFLD. Given that elevated glutamate and BCAAs levels have higher prevalence of NAFLD, we hypothesized that the changes in AAs observed in HPs may be attributed to the impact of NAFLD and IR.